One-deviation principle in coalition formation - Hannu Vartiainen (Aboa Centre for Economics (ACE), 2008)
We study coalitional one-deviation principle in a framework a la Chwe (1994). The principle requires that an active coalition or any of its subcoalition will not benefit from a single deviation to a strategy that specifies, for each history of coalitional moves, an active coalition and its move. A strategy meeting the one-deviation property is characterized. Moreover, it is shown to exist. Finally, the results are compared to the existing theories of coalitional games.
Keywords: C71; C72; 330; one-deviation principle; coalition formation